2022
DOI: 10.1007/s00415-022-11061-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrostructural brain alterations at midlife are connected to cardiovascular and not inherited risk of future dementia: the PREVENT-Dementia study

Abstract: Background Macrostructural brain alterations in the form of brain atrophy or cortical thinning typically occur during the prodromal Alzheimer’s disease stage. Mixed findings largely dependent on the age of the examined cohorts have been reported during the preclinical, asymptomatic disease stage. In the present study, our aim was to examine the association of midlife dementia risk with brain macrostructural alterations. Methods Structural 3T MRI scans were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

6
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 55 publications
3
25
1
Order By: Relevance
“…Structural MRI using ultra high field 7T did not reveal any associations between PI and volumes of brain regions of interest, even at subfield level. This however is consistent with previous findings in presymptomatic familial AD populations (33) and prior PREVENT imaging studies, which did not identify clear patterns of atrophy (34). Considering our participant age (approximately two decades away from predicted dementia onset), the absence of volumetric change may indicate an absence of regional neurodegeneration in this cohort at this early stage in the disease process.…”
Section: Discussionsupporting
confidence: 92%
“…Structural MRI using ultra high field 7T did not reveal any associations between PI and volumes of brain regions of interest, even at subfield level. This however is consistent with previous findings in presymptomatic familial AD populations (33) and prior PREVENT imaging studies, which did not identify clear patterns of atrophy (34). Considering our participant age (approximately two decades away from predicted dementia onset), the absence of volumetric change may indicate an absence of regional neurodegeneration in this cohort at this early stage in the disease process.…”
Section: Discussionsupporting
confidence: 92%
“…Dounavi et al (2020) reported that the volume of the molecular layer of the hippocampus was reduced in cognitively healthy midlife individuals with APOE ε 4 genotype. A more recent study (Dounavi et al, 2022) reported that the hippocampal fissure was enlarged in middle-aged individuals with high CAIDE dementia risk scores. While this accumulating evidence indicates that, individually, the LC and hippocampus are affected in midlife by risk of late-life AD, it remains unknown whether their interactions and joint role in cognition are affected by AD risk at this stage.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol of the PREVENT-Dementia study has been described in detail previously [ 18 , 19 ]. Briefly, participants were recruited from five sites across the UK and Ireland (West London, Edinburgh, Cambridge, Oxford, Dublin).…”
Section: Methodsmentioning
confidence: 99%